Rate of Urea Application and NH3 Volatilization from Loblolly Pine. Issue 1 (14th December 2012) - Kissel, David E.; Cabrera, Miguel L.; Craig, Joseph R.; Rema, John A.; Morris, Larry A.
Abstract : Surface application of urea to pine forests may lead to ammonia (NH3 ) volatilization, which can reduce forest production. The objective of this study was to characterize the effect of rate of urea application on urea hydrolysis rates and the loss of nitrogen (N) by NH3 volatilization under a range of environments in the field. Three field studies were performed in a mid‐rotation loblolly pine ( Pinus taeda L.) plantation with treatments consisting of urea‐N application rates of 50, 100, and 200 kg N ha −1 applied to NH3 volatilization chambers that were designed to adjust the rate of air flow through the system based on wind speed at 1 cm above the soil surface. Overall, there was a tendency during some periods of measurement for urea hydrolysis to be slower at the high rate compared with the lower rates of application, but this effect was small. There was, however, no effect of rate of N application on NH3 loss, expressed as a percentage of the N applied, during any of the three studies. The main factor controlling NH3 loss was water availability as reflected by the interaction between pine needle water potential and relative humidity.